Mechanisms of liquid-phase exfoliation for the production of graphene - Li, Zheling; Young, Robert J.; Backes, Claudia; Zhao, Wen; Zhang, Xun; Zhukov, Alexander A.; Tillotson, Evan; Conlan, Aidan P.; Ding, Feng; Haigh, Sarah J.; Novoselov, Kostya S.; Coleman, Jonathan N. (ACS nano, 2020)
Liquid- phase exfoliation (LPE) is the principal method of producing two-dimensional (2D) materials such as graphene in large quantities with a good balance between quality and cost and is now widely adopted by both the academic and industrial sectors. The fragmentation and exfoliation mechanisms involved have usually been simply attributed to the force induced by ultrasound and the interaction with the solvent molecules. Nonetheless, little is known about how they actually occur, i.e., how thick and large graphite crystals can be exfoliated into thin and small graphene flakes. Here, we demonstrate that during ultrasonic LPE the transition from graphite flakes to graphene takes place in three distinct stages. First, sonication leads to the rupture of large flakes and the formation of kink band striations on the flake surfaces, primarily along zigzag directions. Second, cracks form along these striations, and together with intercalation of solvent, lead to the unzipping and peeling off of thin graphite strips that in the final stage are exfoliated into graphene. The findings will be of great value in the quest to optimize the lateral dimensions, thickness, and yield of graphene and other 2D materials in large-scale LPE for various applications.